Women’s Significant Roles in Pursuing Hotel Revenue: Case of Bali, Indonesia - Ni Made Ary Widiastini; Made Aristia Prayudi (SOSHUM : Jurnal Sosial dan Humaniora, 2021)
This research aims to understand and explain how significant the women’s role in the hotel industry. It is an advanced study which is explores ore from the previous one discussing the women acceptability in the hotel industry in Indonesia, particularly in Bali, with their varied educational background. In fact, this study found that women have significant role in increasing the hotel income through divisions of front office, food and beverage service, and sales. This research was approached qualitatively by conducting depth interviews based on the data that were obtained in 2018 and 2019. As a result, the women in this case tend to have so more hospitality skill that guests feel more comfortable to communicate with them. In addition, the women are also more capable to manage their heart-feeling and to put themselves well according to situations they are in. This capability is then able to persuade the hotel guests to come to the hotels and to have the services. It finally impacts the increasing hotel revenue.